Convertible Debt Financing - Lewellen, Wilbur G.; Racette, George A. (Journal of Financial and Quantitative Analysis, 1973)
The evolution of corporate capital structure theory in the literature of finance has been marked by the development of an increasingly imaginative rendition of market processes under conditions of uncertainty. Trade-offs between debt and equity sources of financing, and their consequent impact on shareholder wealth, have been the major concern. While the evolution is by no means complete, the notion of an efficient capital market in which investor decisions are focused on security portfolio building activities has provided significant insights into the range of opportunities open to corporate management to enhance share valuation through enlightened financing decisions. One measure of the gap between theory and application, however, can be found in the topics which thus far have not been effectively comprehended in the literature, even though the analytical technology is clearly available. Among those topics is the question of convertible debt financing as a capital structure component. The treatment of such a funds source remains essentially in the realm of folklore, the typical story being that convertibles contain the “best elements” of both equity and straight debt or that they provide a vehicle for issuing equity at a “bonus” price higher than the current price. Closer examination reveals that either view is arrant nonsense, and it is to a demonstration of this point that the present paper is addressed.